Monetary policy implementation and overnight rate persistence - Dieter Nautz; Jan Scheithauer (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
Overnight money market rates are the predominant operational target of monetary policy. As a consequence, central banks have redesigned the implementation of monetary policy to keep the deviations of the overnight rate from the key policy rate small and short-lived. This paper uses fractional integration techniques to explore how the operational framework of four major central banks affects the persistence of overnight rates. Our results suggest that a well-communicated and transparent interest rate target of the central bank is a particularly important condition for a low degree of overnight rate persistence.
Keywords: E52; C22; 330; Controllability and Persistence of Interest Rates; Operational Framework of Central Banks; Long Memory and Fractional Integration; Geldpolitik; Mindestreservepolitik; Staatliche Information; Wirkungsanalyse; Tagesgeldmarkt; Zins; Geldmarkt; USA